An ontological model for convocation knowledge in higher education instituation / Madradzi Muhamad - Muhamad, Madradzi (2014)
Knowledge in Higher Education Institution (HEI) does not merely focusing towards teaching and learning. But also, in creating and sharing knowledge. These knowledge not only reside in the subject that been taught in classes but also in their activities. These activities includes program like monthly gathering, convocation ceremony, and others. Convocation, can contribute into a lot of knowledge to HEI. Hence, this research aims to develop the ontology model for convocation knowledge. Knowledge in convocation ceremony is a combination of tacit and explicit knowledge which are scattered and in unorganized state of knowledge. Multiple data source are collected and analyzed consisting the unstructured data comprises of set of interviews and explicit documents. These unstructured data are structured to develop the ontological model for Convocation Knowledge using Protégé. This research contribute in the development of new Ontological Model for Convocation Knowledge which includes four main concept (or classes) which are Convocation Series (ConvoSeries), Convocation Year (ConvoYear), Graduates (Graduates), and Special Award (Special_Award).